Strategi Pemasaran Digital Berbasis Green branding untuk Penguatan UMKM Menuju Ekonomi Berkelanjutan di Kota Pangkalpinang Tahun 2025 - Sumarno Sumarno; Rila Aprylya (Training & Research Institute - Jeramba Ilmu Sukses, 2026)
This study aims to analyze digital marketing strategies grounded in green branding to strengthen the competitiveness of Micro, Small, and Medium Enterprises (MSMEs) and support sustainable economic development in Pangkalpinang City. In the face of the challenges of the digital era and increasing environmental sustainability demands, MSMEs are required to adopt marketing approaches that are not only commercially effective but also environmentally sustainable. This research employs a qualitative approach, using data collection techniques such as in-depth interviews, field observations, and document analysis, with several MSME actors who have implemented green branding principles in their digital marketing activities. The findings reveal that the implementation of green branding-based digital marketing strategies can enhance brand image, increase customer loyalty, and open access to new market segments that are concerned with environmental issues. However, challenges remain, including limited digital literacy, high costs of technology adoption, and limited understanding of sustainability concepts. Therefore, sustained support from local governments, training institutions, and other stakeholders is needed to drive the transformation of MSME marketing toward a greener, more sustainable direction